2012
DOI: 10.1016/j.tra.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of safety-based incentives in Public Private Partnerships: Evidence from the case of Spain

Abstract: Many countries around the world are implementing Public-Private-Partnership (PPP) contacts to manage road infrastructure. In some of these contracts the public sector introduces economic incentives to the private operator to foster the accomplishment of social goals. One of the incentives that have been introduced in some PPP contracts is related to safety in such a way that the better the safety outcome the greater will be the economic reward to the contractor. The aim of this paper is at identify whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…There are differences both in the variable adopted to measure the outcome and in the final formula employed. Most of the contracts include number of injuries, number of fatalities or a combination of number of light accidents, serious accidents and fatal accidents to build the indicator (Rangel, 2011).…”
Section: Cross-country Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…There are differences both in the variable adopted to measure the outcome and in the final formula employed. Most of the contracts include number of injuries, number of fatalities or a combination of number of light accidents, serious accidents and fatal accidents to build the indicator (Rangel, 2011).…”
Section: Cross-country Experiencementioning
confidence: 99%
“…The trunk network is mostly managed in two different ways: free highways, which are built, managed and operated by the central and regional governments (11,000 km); and toll highways (3,016 km), which are managed by private companies through concession contracts (Ministerio de Fomento de España, 2009a). In the last few years some governments in Spain, particularly regional governments, have started to develop PPP contracts based on shadow-toll (Vassallo and Pérez de Villar, 2010;Rangel, 2011) and availability payment approaches (Harding et al, 2010). However, these highways-some of them not yet operational-still represent a small percentage of the trunk network.…”
Section: Toll Highway Concessions In Spainmentioning
confidence: 99%
See 2 more Smart Citations
“…By using a dataset with public and private highways in a cross-section setting for the year 2006, Rangel et al (2012) found that there are more fatalities, injuries and accidents on highways without road safety incentives than on highways with incentives. Also, Rangel et al (2013) evaluated incentive schemes by using data only from private highways between 2007 and 2009, finding that road incentives are significant factors reducing the number of accidents and injuries but not decreasing the number of fatalities.…”
Section: Public-private Partnerships and Road Safety Outcomesmentioning
confidence: 99%